ZAKAT PRODUKTIF DALAM KONTRIBUSI MEWUJUDKAN SDGs NO POVERTY DI KABUPATEN BANJARNEGARA: EFEKTIVITAS PENGELOLAAN - Sugi Fitriyani; Ubaidillah Ubaidillah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the world, the issue of poverty is still a big scourge, including in the Banjarnegara Regency area. Zakat and SDGs have a close relationship related to the goal of poverty alleviation. This study aims to determine the effectiveness of productive zakat management carried out by BAZNAS Banjarnegara Regency in handling poverty and SDGs goals.This research uses descriptive qualitative research methods with the type of field research (field reseacrh). Data collection techniques were conducted through in-depth interviews, observation, documentation, and data analysis. Interviews were conducted with ten of the seventy mustahik recipients of productive zakat assistance in 2022. The results showed that the management realized in productive zakat in Banjarnegara Regency in achieving the SDGs program has continuity in reducing poverty. The pattern used is the utilization of traditional productive zakat through business training and provision of business capital. The form of effectiveness has been seen with an increase in the capital of MSME actors and an increase in income. Productive zakat management has proven to be effective in alleviating poverty and improving mustahik welfare as measured by BKKBN indicators on the concept of family welfare, assisted mustahik have succeeded in fulfilling the Prosperous Family II (KS II) stage.